The Tradition of Congregational Prayer for Forty Consecutive Days; Study of Living Hadith in Kalibening Village Community: Tradisi Shalat Berjamaah Empat Puluh Hari Berturut-Turut; Studi Living Hadis pada Masyarakat Desa Kalibening - Khafidhotul Baroroh; Elvi Tri Astuti Rohmah; Fina Aulika Lestari (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
Allah and His Messenger encourage their people to pray in congregation. In the Kalibening community there is a tradition of praying in congregation for forty consecutive days (Arba'in), which drives Abda 'Abdul Malik as a religious leader in the village of Kalibening. This study aims to determine the theological basis of the hadith related to this tradition, how the community's understanding of the hadith, and how the receptions of the people of kalibening to the Arba'in prayer tradition. This study used a qualitative method, the data were obtained from the results of observations, interviews, questionnaires and documentation, the type of research was living hadith. The results showed that the Arba'in prayer in the Kalibening community departed from the Prophet's command. (Tirmidhi narrative hadith). The Kalibening community understands this hadith textually. Where they perform Arba'in prayers on the grounds that two virtues are promised (freedom from hellfire and hypocrisy). The benefits of performing Arba'in prayers are often encountered by congregations. By performing the Arba'in prayer, the level of religiosity of the Kalibening community has increased, they have become accustomed to praying in congregation, and are more disciplined in time.